In-situ analysis of roman mosaics at Cástulo, lineares (Jaén,Spain): a comparative and non-destructive study - Saelens, Delphine (2019)
The Mosaico de los Amores is an outstandingly well-preserved roman mosaic dating back to the end of the 1st and beginning of the 2nd century CE. Due to the remarkable preservation state and the technical quality, the mosaic forms an important part of cultural heritage. Handheld X-ray Fluorescence (hXRF) and Raman spectroscopy were employed to analyse the material composition of the mosaic tesserae to get insight in the production technology and raw materials used. These techniques can also determine the conservation state of the mosaic as weathering products can be detected. The thesis contributes to the preventive conservation of the Mosaico de los Amores. Additionally, this thesis aims to compare different Raman instruments and their lasers and their suitability in the field for analysing cultural heritage. A total of 144 tesserae originating from two scenes of the mosaic are discussed in this thesis. The elemental and mineralogical compositions are discussed revealing two major groups, glass and stone tesserae. The stone tesserae with a high Ca content are made from carbonaceous stones, which were abundant in the their locality of the site. The colorants and opacifiers used to produce the different glass colours were identified with the hXRF results since the Raman results on the glasses were limited. The results gave insights in the production technology of Roman glasses. Furthermore, the comparison of the different Raman instruments yielded interesting results; Resumo: O Mosaico de los Amores é um mosaico Romano excepcionalmente bem preservado que remonta ao fim do primeiro e início do Segundo século DC. O notável estado de conservação e a qualidade técnica fazem deste mosaico uma parte importante do patrimônio cultural. Espectroscopia de Fluorescência de Raios-X (hXRF) e espectroscopia Raman foram empregadas para analisar a composição material das tesselas do mosaico e obter uma percepção na tecnologia de produção e as materiais utilizados. Essas análises também podem determinar o estado de conservação do mosaico e os produtos de intemperismo podem ser detectados. A tese contribui para a conservação preventiva do Mosaico de los Amores. Além disso, esta tese tem como objectivo comparar diferentes instrumentos Raman e seus lasers no campo de análise do património cultural. Um total de 144 tesselas provenientes de duas cenas do mosaico são discutidas nesta tese. As composições elementares e mineralógicas são discutidas revelando dois grupos principais: tesselas de vidro e de pedra. As tesselas de pedra apresentam um alto teor de Ca, sendo feitas a partir de pedras carbonosas, que eram abundantes na localidade. Os corantes e opacificantes utilizados para produziras diferentes cores de vidro forma identificados com os resultados de hXRF já que os resultados obtidos por Raman foram limitados. Os resultados também deram uma compreensão sobra a tecnologia de produção de vidros romanos. Além disso, a comparação dos diferentes instrumentos Raman produziu resultados interessantes.